A new institutional and normative structure: Urban and housing policy in São Bernardo do Campo/SP - Godoy, Jeane Aparecida Rombi de (Electronic Journal "Fórum Ambiental da Alta Paulista", 2023)
This article carried out an analysis of the urban and environmental legislation applicable to the protection spaces in the water sources of the Billings Reservoir in the face of the institutionalization of the water protection laws, highlighting the management process and its developments in the face of the emergence of the socio-environmental recovery of the APRMs. In this region, the connection between the accelerated process of industrialization, disorderly urbanization and the increase in population concentration observed over the years, devoid of adequate planning and territorial ordering actions, is notorious in this region, which contributed to the intensification of socio-spatial inequalities. sustained by a pattern of exploitation and dilapidation of uses and degradation of ecosystems. For this purpose, the main environmental and urban regulations were analyzed, as well as the actions resulting from legislation and urban and environmental public policies implemented in São Bernardo do Campo. For its development, we started with the object of study chosen by this research, the APPs (essential components of spring ecosystems), considering the geophysical attributes that characterize the municipality of São Bernardo do Campo, where 52% of its territory is located, inserted in areas protecting the water sources of the Billings Dam. Thus, we sought to identify aspects related to the treatment of watershed protection and recovery areas, specifically those that aim to achieve urban sustainability.